1993
DOI: 10.1152/jn.1993.69.1.248
|View full text |Cite
|
Sign up to set email alerts
|

Membrane currents evoked by afferent fiber stimulation in rat piriform cortex. I. Current source-density analysis

Abstract: 1. The membrane currents evoked by afferent fiber stimulation in the piriform cortex were derived by the use of current source-density (CSD) analysis in the rat under urethan anesthesia. The primary goals were to test hypotheses concerning the sequence of synaptic events evoked by afferent fiber stimulation and to derive data required for development and testing of the model presented in the companion paper. 2. In confirmation of previous studies, it was found that afferent fiber stimulation evokes a monosynap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 0 publications
10
71
1
Order By: Relevance
“…CSD analysis demonstrated that the onset of the odorinduced Ib sink (period 1) was followed by a small sink in layer II-III coupled to a reinforcement of the Ib sink. In line with the previous studies by the Haberly group, the layer II-III sink could be attributed to an inhibitory, possibly feedback, potential (Ketchum and Haberly 1993b;Neville and Haberly 2004). Even though the definitive confirmation of the existence of an inhibitory component in the response could be attained by intracellular recordings, extracellular unit recordings performed in our study strongly support this conclusion.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…CSD analysis demonstrated that the onset of the odorinduced Ib sink (period 1) was followed by a small sink in layer II-III coupled to a reinforcement of the Ib sink. In line with the previous studies by the Haberly group, the layer II-III sink could be attributed to an inhibitory, possibly feedback, potential (Ketchum and Haberly 1993b;Neville and Haberly 2004). Even though the definitive confirmation of the existence of an inhibitory component in the response could be attained by intracellular recordings, extracellular unit recordings performed in our study strongly support this conclusion.…”
Section: Discussionsupporting
confidence: 89%
“…The laminar profile of LFPs obtained by LOT stimulation in this preparation (Fig. 3A) was very similar to those described in the previous studies (Biella et al 1996a,b;Ketchum and Haberly 1993b). Then, we compared the initial component of the odor-induced response with LOT-evoked response sequentially recorded at identical cortical depths.…”
Section: Odor-induced Local Field Potential In Apc Dsupporting
confidence: 81%
See 2 more Smart Citations
“…More recently, these concepts have been merged into the proposition of the anterior piriform cortex (aPC) as a "hybrid recurrent/feedforward pattern correlation network" (Haberly, 2001). In vivo current source density analysis in the aPC revealed the sequential activation of sensory and intracortical synapses on aPC principal cells (Ketchum and Haberly, 1993).…”
Section: Introductionmentioning
confidence: 99%